The effects of reflective writing on EFL student-teachers’ critical thinking: a quasi-experimental study - Gemechu Tola Chala; Adinew Tadesse Degago; Abera Admassu Endashaw; Alemayehu Getachew Tsegaye (Humanities & Social Sciences Communications)
Abstract Critical thinking (CT) enables EFL students in Ethiopia to analyze language, solve problems, and adapt to academic and real-life challenges, while reflective writing (RW), as an independent variable, supports them to think and reflect about experiences to learn better. This study examined English as a Foreign Language (EFL) student-teachers’ CT using a quasi-experimental method. The participants were first-year second-semester EFL diploma trainees at Asella College of Teacher Education (ACTE), comprising two intact groups: an experimental group (D1) and a control group (D2). The study employed MANCOVA (Analysis of covariates) as a statistical model, considering age, Ethiopian University Entrance Examination (EUEE), and pretest results. In addition, the California Critical Thinking Skills Test (CCTST) was used to assess both the students’ prior skills and post-intervention. The MANCOVA analysis revealed that RW significantly improved all aspects of CT with p < 0.001 and a large effect size (η2 = 0.691) compared to the control group. However, the most substantial gains were observed in Analysis (η2 = 0.540) and Interpretation (η2 = 0.507), while Evaluation (η2 = 0.282), Explanation (η2 = 0.352), and Inference (η2 = 0.396) improved less. This indicates the effects of RW are more noticeable in reasoning skills, while other higher-order thinking skills may need other targeted instructional support. Finally, age and EUEE had no influence on outcomes, while students with better initial CT benefited more from RW. This indicates that RW for cognitive growth may benefit learners across diverse backgrounds and academic profiles. In conclusion, integrating RW into EFL education is particularly timely and relevant in Ethiopia’s shift toward a competency-based curriculum and the cultivation of skilled professionals. Thus, this study suggests that as CT becomes an essential skill for the current education, the insights gained from Ethiopia’s classrooms offer valuable guidance for education systems facing similar constraints globally.